Multiteam Systems in Long Duration Exploration Missions: A Qualitative Analysis of Key Characteristics and Challenges - Verhoeven, Dana C.; Kramer, William S.; Shuffler, Marissa L. (Frontiers in Psychology, 2022)
Given the unprecedented environment of long duration exploration missions (LDEMs), success simply cannot occur without the coordinated efforts of multiple teams, both in flight and on the ground. These multiteam systems (MTSs) are needed to achieve the complex and dynamic tasks of spaceflight missions that will be longer and more uncertain than any previously experienced. Accordingly, research is limited in terms of how to best coordinate these teams and their dynamics—and in particular, how to best prepare LDEM teams to work across time and space effectively. To begin to address these critical questions systematically, qualitative data was extracted from a series of ten interviews with experts in spaceflight and long duration analog environments. Using thematic analysis techniques, we identified several consistent themes for affective, behavioral, and cognitive elements of teamwork occurring within and between teams. We examine each of these in detail, to identify the dynamics of what is currently known and where research needs to go to provide guidance for spaceflight organizations as well as others attempting to successfully implement MTSs in novel, complex environments.